Predicting Neonatal Encephalopathy From Maternal Data in Electronic Medical Records - Li, Thomas (AMIA Jt Summits Transl Sci Proc, 2018)
Neonatal encephalopathy (NE) is a leading cause of neonatal mortality and lifetime neurological disability. The earlier the risk of NE can be assessed, the more effective interventions can be in preventing adverse outcomes. Existing studies that focus on intrapartum risk factors do not provide the early prognostic forecasting necessary to prepare healthcare professionals to intervene early in a high-risk NE case. This work used maternal data in a supervised machine learning framework to predict NE events. Specifically, we 1) collected the electronic medical records (EMRs) for 104 NE newborns and 31,054 non-NE newborns and their mothers, 2) trained and tested a regularized logistic regression on imbalanced and high-dimensional EMR data, and 3) discerned important features that could be possible risk factors. The learned model offers prenatal predictions of NE cases with an average area under the receiving operator characteristic curve (AUC) of 87% and identified the most important predictors.